89.4k views
0 votes
What is equivalent to the polynomial (4x+3)(3x-8)

2 Answers

2 votes


= > (4x + 3)(3x - 8) \\ \\ = > 4x * 3x - 4x * 8 + 3x * 3 - 8 * 3 \\ \\ = > 12 {x}^(2) - 32x + 9x - 24 \\ \\ = > 12 {x}^(2) - 23x - 24
User Hbas
by
5.9k points
1 vote
The equivalent polynomial is 12x^2 -23x - 24.

You can get this by multiplying the two parenthesis by each other.

First start by multiplying the two front numbers:
4x * 3x = 12x^2

Then multiply the outermost numbers:
4x * -8 = -32x

Then multiply the innermost numbers:
3x * 3 = 9x

Then multiply the last numbers:
3* -8 = -24

Now combine all of them to get the above polynomial.
User Shumon Saha
by
5.4k points